A checklist of chiggers (Trombidiformes: Trombiculidae and Leeuwenhoekiidae) of Panama - Bassini-Silva, Ricardo [UNESP] (2021)
An updated checklist of chiggers from the family Trombiculidae and Lecuwenhockiidae is presented, with 81 species in 38 genera parasitizing different terrestrial vertebrate hosts in Panama. The depository for all Panamanian records, including new localities and host-associations records for the species Blankaartia sinnamaryi (Floch and Fauran. 1956), Eutrombicula tinami (Oudemans, 1910), Eutrombicula goeldii (Oudemans, 1910), Hooperella vesperuginis (Brennan and Jones, 1960), and Pseudoschoengastia bulbiftra Brennan. 1960 were provided.